019 Life events in the year preceding the onset of conversion disorder: the role of the type and timing of events. Issue 10 (24th September 2010) - Aybek, S; Nicholson, T; Craig, T; David, A; Kanaan, R
Abstract : Aims: Classical models of Conversion Disorder (CD) hypothesise that specific stressful experiences are "converted" into symptoms to relieve psychological pressure, and would suggest those experiences should be of a nature that allowed the "escape" from an unwelcome situation and would also tend to be underreported by patients. We sought to compare the frequency of severe life events preceding illness onset in a series of CD patients with those occurring in a healthy control group, and to characterise the nature of those events in two dimensions: "escape" and "underreporting". Methods: In this prospective study we use the Life Events and Difficulties Schedule (LEDS) to look for adverse life events in the year preceding illness onset in patients with conversion disorder, and in a matched epoch in healthy controls. The LEDS is a validated and reliable semi-structured interview designed to minimise recall and interviewer bias through rigorous assessment and independent rating of the severity of events. It permits contextual objective ratings of events that can be contrasted to the subjective severity reported by the subject. It also permits the evaluation of an "escape" component, defined as the extent to which subsequent illness could alter the consequences of the event and bestow advantage on the sufferer. All ratings were made by an expert panel blinded to clinical status. The patients were referred by neurologists from local hospitals; controls of the same age and gender were randomly selected from a local GP database. Results: Preliminary results on 14 CD patients (mean age 34) and 9 controls (mean age 36) revealed a higher occurrence of severe events in CD patients (mean 1/year) as compared to controls (mean 0.5/year) (p<0.05). There was a clustering of these events in the 3 months preceding illness onset in CD, with a mean of 0.86 events per month in the last 3 months compared to 0.04 per month in the preceding period (p<0.01). A significant "escape" component was found in the events of 9 patients (64%), but in only 2 controls (22%). A tendency to under-report those severe events emerged in 28% of CD patients, when it occurred in 11% of controls. Our preliminary sample size meant the latter differences, though clinically striking, did not reach statistical significance. The ongoing recruitment of new subjects will allow definite conclusions in the near future. Conclusions: Preliminary data from this ongoing study suggest that the time frame (preceding 3 months), the nature ("escape"), and the tendency to underreport events may play important roles in identifying key events related to CD onset. They support the post-Freudian theory of a psychological stressor being converted to a symptom in order to bring some relief to the patient, providing a more convenient situation (escape or secondary gain) and a less traumatic memory of the event.